Review Paper on Economic Growth–Aggregate Energy Consumption Nexus - Isa, Zaidi; Alsayed, Ahmed R.M.; Kun, Sek Siok (International Journal of Energy Economics and Policy, 2015)
The aim of this study is to survey the empirical studies which interested in detecting the causal relationship between energy consumption and economic growth, and to provide some recommendations to policymakers for designing the environmental policies and policy implications of effective energy. Our review paper concentrates to make a survey depending on included variables in the studies, thus it has been classified into two groups; bivariate framework and multivariate framework. The results show that the multivariate studies support the feedback hypothesis more than the bivariate studies with (45.7%) and (29.5%) respectively. In contrast of that in neutrality hypothesis, the bivariate framework studies support it with (26.2%) which is more than that in multivariate framework (12.1%) only. In the other hand the results by considering the whole empirical studies in our survey support the hypotheses as the following; (34.3%), (24.0%), (19.7%) and (22.0%) for the feedback, growth, conservation and neutrality hypothesis respectively. Moreover we provide some suggestions for future studies; it should focuses more on new approaches consist the multivariate framework rather than by applying common methods with the same variables in bivariate framework only, which could be solved by adding unprecedented variables such as technology innovation, index investment and environmental quality with applying environmental Kuznets curve (EKC). In the analysis should considers the possibility of structural breaks, the coefficients signs, and distinguish between the short and long run causality relationship. And it should include two distinct groups of energy consumption; renewable and nonrenewable energy rather than aggregate or disaggregate energy consumption. Keywords: Economic growth; aggregate energy consumption; causality relationship. JEL Classifications: Q4; Q43